Peran Media Sosial dalam Meningkatkan Interaksi Pembelajaran di Kalangan Mahasiswa Universitas Madako Tolitoli - Ikbal, Ikbal; Saugadi, Saugadi (LPPM Universitas Madako Tolitoli, 2025)
This research aims to investigate the role of social media in enhancing learning interactions among students at Universitas Madako Tolitoli. In the era of the Fourth Industrial Revolution, the development of information and communication technology has transformed the educational paradigm, where social media serves not only as a means of entertainment but also as an effective tool to support the learning process. Through qualitative research methods involving in-depth interviews and focus group discussions, this study identifies patterns of social media usage among students, as well as the challenges and opportunities faced in the academic context. The results show that platforms like WhatsApp, Facebook, and Instagram have enhanced collaboration and communication between students and lecturers, as well as among the students themselves. Social media facilitates rapid information exchange and creates a more interactive learning environment. However, challenges such as distractions and the spread of inaccurate information have also been identified, which can affect learning effectiveness. Therefore, it is essential for educational institutions to formulate clear social media usage policies, provide media literacy training, and integrate social media into the curriculum. This research is anticipated to aid in the creation of more innovative learning strategies that align with the needs of today's digital generation, while also motivating Universitas Madako Tolitoli to utilize social media as a strategic educational tool. With an appropriate approach, social media has the potential to foster more productive academic interactions and establish an adaptive and collaborative learning culture within higher education settings. Keywords : Social Media, Learning Interactions, Qualitative Research, In-Depth Interviews, Focus Group Discussions, Educational Paradigm, Information and Communication Technology, Interactive Learning Environment, Distractions in Learning